การพัฒนาโปรแกรมการศึกษานอกระบบโรงเรียนเพื่อพัฒนาสมรรถนะอาชีพผู้ดูแลสุขภาพในสปา - กนกพร แสงปัญญารักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of the research were: (1) to develop a non-formal education program for enhancing the career competency for spa therapists, (2) to implement a developed non-formal education program for enhancing career competency for spa therapists, (3) to analyze the relevant factors affecting the developed program. The research procedures were divided into three steps: (1) to develop a non-formal education program for enhancing career competency for spa therapists by needs assessment survey on problems and learning needs of 120 spa therapists who were achieved a vocational traditional Thai massage course from non-formal and informal education centers, (2) to study the result of the developed program implementation. The samples of the study consisted of 44 spa therapists who were achieved a vocational traditional Thai massage course from district non-formal and informal education centers. They were divided into 2 groups: an experimental group and a control group. An experimental group consisted of 22 spa therapists who were trained by the developed program, while the control group was consisting of 22 spa therapists who attended the normal program with the normal teaching method, and (3) to analyze the relevant factors affecting the developed program from group discussion of the experimental group. The research findings were as follows: 1. The non-formal education program to enhance career competency for spa therapists was consisted of 9 factors namely: objectives, learners, facilitators, content, learning activities, learning period, learning resources and media, environment, evaluation and assessment. 2. The results of the developed non-formal education program implementation were as follows: (1) The score of the knowledge in the communicative Chinese language for spa therapists and ten trigger-point therapy after the experimentation increased higher than the prior experimentation with statistical significant at level of .05 , (2) The score of the Chinese language communicative skill for spa therapists and ten trigger-point therapy skill after the experimentation increased higher than the prior experimentation with statistical significant at level of .05, (3) The score of the Chinese language attitude for spa therapists and the spa therapist career attitude after the experimentation increased higher than the prior experimentation with statistical significant at level of .05. 3. The relevant factors affecting the developed program of this research were composed of: (1)The motivation and learning intention of learners, (2) The readiness and positive attitude of an instructor or a group teacher assistants, (3) The learning activities with scaffolding by writing daily recording, (4) The simply contents and self-revision with learning manual, (5) The frustration reduction by encouraging learning atmosphere and environment. Conditions of the developed program were composed of: (1) The learning needs of learners, (2) The suitable numbers of learners for practicing, (3) A minimum of one year of working experience in a professional massage or spa.